Fe-Mn alloy, hairspring for timepiece, and method for manufacturing Fe-Mn alloy

By using a specific component's Fe-Mn alloy, and through thermal processing, cold processing, and curing heat treatment, clocks are used to solve the problem of strong response and impact resistance of existing scarlet materials to the magnetic field, and realize the low magnetization rate and excellence The effect of processability.

CN119384520APending Publication Date: 2025-01-28CITIZEN WATCH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380047070.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-17
Filing Date
2023-06-08
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing hairspring material for watches has a strong reaction to the magnetic field, and the hairspring using glass or silicon has problems with impact resistance.

Method used

The FE-MN alloys are used as a hooded material, and their composition includes manganese greater than 30.0 % and less than 35.0 %, aluminum of 1.0 % or less or less, carbon of 0.5 % or less, 5.0 % less than 10.0 % chromium, 2.5, 2.5 Nickels with a nickel of more than 5.0 % and less than 5.0 % have γ-FE phase or β-Mn as the crystal structure, and are made of heat processing, cold processing and solidifying heat treatment process.

Benefits of technology

The FE-Mn alloy has a low magnetization rate and excellent processingability. It is suitable for watch with watches. It is not strong and easy to damage to the magnetic field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119384520A_ABST
    Figure CN119384520A_ABST
Patent Text Reader

Abstract

Provided is an Fe-Mn alloy having low susceptibility and excellent workability. The Fe-Mn alloy has a component composition containing, in mass%, more than 30.0% and 35.0% or less of manganese (Mn), 1.0% to 8.0% of aluminum (Al), 0.5% to 1.5% of carbon (C), 5.0% to 10.0% of chromium (Cr), 2.5% to 5.0% of nickel (Ni), and the balance of iron (Fe), and has a gamma-Fe phase or a beta-Mn phase as a crystal structure, the sum of the area fraction of the [gamma]-Fe phase and the area fraction of the [beta]-Mn phase is 50% or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an Fe-Mn alloy, a hairspring for a watch, and a method for manufacturing the Fe-Mn alloy. Background Art

[0002] In recent years, the magnetic environment of precision instruments has changed significantly. Magnets are used in electronic devices such as smartphones and tablet terminals, as well as their chargers, covers, and housings, and the chances of precision equipment being exposed to high magnetism have increased more than before. Therefore, for precision instrument parts such as watches, in addition to being small, thin, and highly rigid, they are also required to have properties that are difficult to react to magnetic fields.

[0003] In the past, alloys containing elements such as iron or cobalt as the main raw materials were used as the material of the hairspring in the speed regulating mechanism of mechanical clocks. Since these alloys are ferromagnetic, they have the property of reacting strongly to magnetic fields. On the other hand, it has been proposed to use non-metallic materials such as glass or silicon as materials that do not react to magnetic fields to manufacture hairsprings. However, since glass and silicon are brittle materials, hairsprings using these materials have problems in terms of impact resistance.

[0004] Patent Document 1 describes an antiferromagnetic alloy mainly made of iron and used in the movement parts of a watch. The antiferromagnetic alloy of Patent Document 1 has the following composition: 10.0 wt% to 30.0 wt% of manganese, 4.0 wt% to 10.0 wt% of chromium, 5.0 wt% to 15.0 wt% of nickel, 0.1 wt% to 2.0 wt% of titanium, the remainder being iron and residual impurities, and not containing beryllium. Prior art literature Patent Literature

[0005] Patent Document 1: Japanese Patent Application No. 2020-501006 Summary of the invention

[0006] An object of the present invention is to provide an Fe-Mn alloy having low magnetic susceptibility and excellent workability, a timepiece hairspring, and a method for producing the Fe-Mn alloy.

[0007] The Fe-Mn alloy according to the embodiment of the present invention is characterized in that, as a component composition, it contains, in mass%, manganese (Mn) greater than 30.0% and less than 35.0%, aluminum (Al) greater than 1.0% and less than 8.0%, carbon (C) greater than 0.5% and less than 1.5%, chromium (Cr) greater than 5.0% and less than 10.0%, nickel (Ni) greater than 2.5% and less than 5.0%, and the remainder is iron (Fe), and has a γ-Fe phase or a β-Mn phase as a crystal structure, and the sum of the area fraction of the γ-Fe phase and the area fraction of the β-Mn phase is greater than 50%.

[0008] The Fe-Mn alloy according to an embodiment of the present invention is characterized in that, as a component composition, it contains, by mass%, 25.0% to 30.0% of manganese (Mn), 1.0% to 8.0% of aluminum (Al), 0.5% to 1.5% of carbon (C), more than 10.0% and 15.0% of chromium (Cr), 2.5% to 5.0% of nickel (Ni), and the remainder is iron (Fe), and has a γ-Fe phase or a β-Mn phase as a crystal structure, and the sum of the area fraction of the γ-Fe phase and the area fraction of the β-Mn phase is 50% or more.

[0009] In addition, in the Fe-Mn alloy, the magnetic susceptibility is preferably 0.030 or less.

[0010] In the Fe—Mn alloy, the sum of the area fraction of the γ-Fe phase and the area fraction of the β-Mn phase is preferably 80% or more.

[0011] In the Fe—Mn alloy, the area fraction of the β-Mn phase is preferably larger than the area fraction of the γ-Fe phase.

[0012] A timepiece hairspring according to an embodiment of the present invention is characterized in that it is formed of the Fe—Mn alloy according to an embodiment of the present invention.

[0013] The method for producing an Fe-Mn alloy according to an embodiment of the present invention is characterized in that it includes: a hot working step of hot working an ingot to obtain a hot-worked product, a cold working step of cold working the hot-worked product to obtain a cold-worked product, and a solidification heat treatment step of solidifying the cold-worked product to obtain an Fe-Mn alloy, wherein the component composition of the Fe-Mn alloy includes, in terms of mass%, manganese (Mn) greater than 30.0% and less than 35.0%, aluminum (Al) greater than 1.0% and less than 8.0%, carbon (C) greater than 0.5% and less than 1.5%, chromium (Cr) greater than 5.0% and less than 10.0%, nickel (Ni) greater than 2.5% and less than 5.0%, and the remainder is iron (Fe), and the alloy has a γ-Fe phase or a β-Mn phase as a crystal structure, and the sum of the area fraction of the γ-Fe phase and the area fraction of the β-Mn phase is 50% or more.

[0014] The method for producing an Fe-Mn alloy according to an embodiment of the present invention is characterized in that it includes: a hot working step of hot working an ingot to obtain a hot-worked product, a cold working step of cold working the hot-worked product to obtain a cold-worked product, and a solidification heat treatment step of solidifying the cold-worked product to obtain a magnetic-resistant Fe-Mn alloy, wherein the component composition of the Fe-Mn alloy includes, by mass%, 25.0% to 30.0% of manganese (Mn), 1.0% to 8.0% of aluminum (Al), 0.5% to 1.5% of carbon (C), more than 10.0% and 15.0% of chromium (Cr), 2.5% to 5.0% of nickel (Ni), and the remainder is iron (Fe), and the alloy has a γ-Fe phase or a β-Mn phase as a crystal structure, and the sum of the area fraction of the γ-Fe phase and the area fraction of the β-Mn phase is 50% or more.

[0015] According to the present invention, there are provided an Fe-Mn alloy having low magnetic susceptibility and excellent workability, a timepiece hairspring, and a method for producing the Fe-Mn alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 1 is a diagram showing the appearance of the hairspring 1 . Figure 2 1 is a flowchart showing the flow of a method for manufacturing the hairspring 1 . Figure 3 (A) is a diagram showing a SEM image of a Fe-Mn alloy of a comparative example, Figure 3 (B) is a diagram showing a SEM image of the Fe—Mn alloy of the example. DETAILED DESCRIPTION

[0017] Figure 1 The appearance of a hairspring 1 for a timepiece according to an embodiment of the present invention is shown. The hairspring 1 is used in a regulating mechanism of a mechanical timepiece.

[0018] The hairspring 1 is formed by processing the Fe-Mn alloy of the first embodiment. The Fe-Mn alloy of the first embodiment has a component composition of more than 30.0% and less than 35.0% manganese (Mn), 1.0% to 8.0% aluminum (Al), 0.5% to 1.5% carbon (C), 5.0% to 10.0% chromium (Cr), 2.5% to 5.0% nickel (Ni), and the remainder is iron (Fe) and unavoidable impurities, and has a γ-Fe phase or a β-Mn phase as a crystal structure, and the sum of the area fraction of the γ-Fe phase and the area fraction of the β-Mn phase is 50% or more.

[0019] Fe-Mn alloy has α phase and γ-Fe phase or β-Mn phase as crystal structure. α phase is composed of cubic crystal structure, and the lattice spacing is The number of atoms in the unit cell is 2. The γ-Fe phase is also called the austenite phase. The γ-Fe phase is paramagnetic. The β-Mn phase is composed of a cubic crystal structure with a lattice spacing of The number of atoms in the unit cell is 20. β-Mn phase is paramagnetic.

[0020] The Fe—Mn alloy has a low magnetic susceptibility because it has a γ-Fe phase or a β-Mn phase as a crystal structure.

[0021] Hereinafter, the Fe—Mn alloy according to the first embodiment will be described in more detail.

[0022] Fe-Mn alloy contains Mn greater than 30.0% and less than 35.0% by mass. Mn forms a solid solution with a crystal structure of γ-Fe phase with Fe. The γ-Fe phase is transformed into the β-Mn phase by processing and solidification heat treatment. As a result, the Fe-Mn alloy has a low magnetic susceptibility and good processability. That is, if the γ-Fe phase and the β-Mn phase are too few, the ratio of the α phase increases, so the magnetic susceptibility of the Fe-Mn alloy becomes high.

[0023] The Fe-Mn alloy contains 1.0% to 8.0% Al by mass. Al forms a solid solution with an α-phase crystal structure with Fe. As a result, the workability of the Fe-Mn alloy is excellent. In addition, if the amount of Al is too small, the workability of the Fe-Mn alloy is impaired. In addition, since Al is paramagnetic, it does not affect the magnetic susceptibility of the Fe-Mn alloy.

[0024] Fe-Mn alloy contains 0.5% to 1.5% C by mass. C penetrates into Fe and stabilizes the crystal structure of γ-Fe phase. γ-Fe phase transforms into β-Mn phase through processing and aging heat treatment. In addition, C improves the workability of Fe-Mn alloy. When the amount of C is too much, M3C, M 23 Carbides such as C6 (M is Fe, Mn or Cr) precipitate, making the Fe-Mn alloy brittle.

[0025] The Fe-Mn alloy contains 5.0% to 10.0% Cr in mass%. Cr and Fe form a solid solution having a γ phase crystal structure. The γ-Fe phase transforms into the β-Mn phase through processing and aging heat treatment. In addition, Cr mainly exists as carbides at the boundary between the β-Mn phase and the α phase, which increases the hardness of the Fe-Mn alloy. In addition, Cr forms an oxide film layer on the surface of the Fe-Mn alloy, which helps to improve the corrosion resistance. That is, when the amount of Cr is too small, the oxide film layer cannot be fully formed, and the corrosion resistance is reduced. When the amount of Cr is too much, the hardness of the Fe-Mn alloy is excessive and the processability is impaired.

[0026] The Fe-Mn alloy contains 2.5% to 5.0% Ni by mass. Ni and Fe form a solid solution having an α-phase crystal structure. In addition, Ni improves the forging workability of the Fe-Mn alloy during hot working and / or cold working.

[0027] The remainder of the Fe-Mn alloy is Fe. The remainder being Fe means that, in addition to Fe, the composition also contains inevitable impurities. Inevitable impurities are impurities that are inevitably mixed from raw materials, etc., or are unintentionally and inevitably mixed in the manufacturing process. Examples of inevitable impurities are Si (silicon), P (phosphorus), S (sulfur), etc. By making the inevitable impurities less than 0.1% by mass, the influence on the properties of the Fe-Mn alloy becomes slight. In addition, in order to not affect the properties of the Fe-Mn alloy even if the inevitable impurities are concentrated in a part of the alloy, it is preferably less than 0.01% by mass.

[0028] The Fe-Mn alloy contains an α phase and a γ-Fe phase or a β-Mn phase as a crystal structure. Preferably, at least a portion of the γ-Fe phase or the β-Mn phase contained in the Fe-Mn alloy is observed to have an area of ​​1 μm in the SEM image. 2 That is, in the Fe-Mn alloy, the γ-Fe phase or the β-Mn phase is not a fine precipitate, but exists as the main crystal structure. As a result, the Fe-Mn alloy has a low magnetic susceptibility and excellent workability.

[0029] In Fe-Mn alloy, the sum of the area fraction of γ-Fe phase and the area fraction of β-Mn phase is more than 50%. Therefore, Fe-Mn alloy has low magnetic susceptibility and good processability. The area fraction is obtained by measuring the area of ​​α phase, γ-Fe phase and β-Mn phase contained in a specific size area (for example, 100μm×100μm area) in SEM image observation.

[0030] In Fe-Mn alloy, by making the area fraction of the region other than α phase, γ-Fe phase and β-Mn phase less than 10%, the hardness of Fe-Mn alloy will not be too high, so it is possible to prevent the workability in hot working and cold working from being impaired. In Fe-Mn alloy, by making the area fraction of the region other than α phase, γ-Fe phase and β-Mn phase less than 1%, it is possible to suppress the discovery of phases showing magnetism in Fe-Mn alloy, and the magnetic susceptibility can be further reduced. The region other than α phase, γ-Fe phase and β-Mn phase is, for example, a region corresponding to carbides such as Cr carbide. If the area fraction of the region other than α phase, γ-Fe phase and β-Mn phase is the above-mentioned area fraction, the influence on the properties of Fe-Mn alloy is slight.

[0031] The hairspring 1 can also be formed by processing the Fe-Mn alloy of the second embodiment. The Fe-Mn alloy of the second embodiment has a component composition that includes, by mass%, 25.0% to 30.0% of manganese (Mn), 1.0% to 8.0% of aluminum (Al), 0.5% to 1.5% of carbon (C), more than 10.0% to 15.0% of chromium (Cr), 2.5% to 5.0% of nickel (Ni), and the remainder is iron (Fe), and has a γ-Fe phase or a β-Mn phase as a crystal structure, and the sum of the area fraction of the γ-Fe phase and the area fraction of the β-Mn phase is 50% or more.

[0032] The difference between the Fe-Mn alloy of the second embodiment and the Fe-Mn alloy of the first embodiment is that the composition of Mn is small and the composition of Cr is large. That is, the Fe-Mn alloy of the second embodiment is to reduce the amount of Mn in the Fe-Mn alloy of the first embodiment and increase the amount of Cr instead. Cr has a property similar to that of Mn in that it forms a solid solution with a crystal structure of γ phase with Fe. Therefore, the Fe-Mn alloy of the second embodiment has a low magnetic susceptibility and excellent processability, similar to the Fe-Mn alloy of the first embodiment.

[0033] <Method for manufacturing hairspring> Figure 2: is a flowchart showing the process of the manufacturing method of the hairspring 1. The manufacturing method includes: an ingot melting process (step S1), a hot working process (steps S2-S3), a cold working process (steps S4-S6), a plastic working process (step S7), and a solidification heat treatment process (step S8). In the ingot melting process, the ingot is melted. In the hot working process, the ingot is hot worked to produce a hot-worked product. In the cold working process, the hot-worked product is cold worked to produce a cold-rolled material having a metal crystal with introduced dislocations. The cold-rolled material includes a γ-Fe phase and an α phase as a crystal structure. In the solidification heat treatment process, the cold-rolled material is solidified and heat-treated to produce an Fe-Mn alloy. If dislocations are introduced into the metal crystal in the cold working process, a phase transition from the γ-Fe phase to the β-Mn phase occurs in the solidification heat treatment process.

[0034] First, an ingot is melted (step S1). The ingot is made by dissolving weighed raw materials so as to obtain a predetermined component composition, and then pouring the ingot into a mold for melting. The raw materials are melted using, for example, a high-frequency vacuum melting device.

[0035] Dissolution using a high-frequency vacuum dissolution device is performed, for example, as follows. First, a ceramic crucible containing weighed raw materials is loaded into a heating unit in the device. The heating unit has a mechanism that enables pouring as described below. In addition, a mold at room temperature is also provided in the device. The device is set to 1×10 -2 [Pa] or less, fill with inert gas. The inert gas is, for example, nitrogen or argon. In an inert gas atmosphere, the raw material is subjected to high-frequency induction heating. By heating for 10 to 45 minutes, the raw material is softened and dissolved, and the raw material becomes a liquid molten metal state. Then, the heating state is maintained for 5 to 25 minutes so that the temperature of the molten metal reaches a temperature range of 1400 to 2000°C. In addition, the temperature of the molten metal can be measured by immersing a thermocouple protected by a heat-resistant component in the molten metal. After being maintained in the heated state, the molten metal is poured into a mold at room temperature and quenched. After quenching, it is allowed to stand for 4 to 9 hours, and the molten metal is cooled to room temperature to form a solid ingot. After standing, the inside of the device is set to a vacuum atmosphere, and then opened to the atmosphere. In this way, the ingot can be taken out of the mold.

[0036] When manufacturing the Fe-Mn alloy of the first embodiment, the specified component composition of the ingot contains, in mass %, more than 30.0% and less than 35.0% of Mn, 1.0% to 8.0% of Al, 0.5% to 1.5% of C, 5.0% to 10.0% of Cr, 2.5% to 5.0% of Ni, and the remainder is Fe.

[0037] When manufacturing the Fe-Mn alloy of the second embodiment, the specified component composition of the ingot includes, in mass %, 25.0% to 30.0% manganese Mn, 1.0% to 8.0% Al, 0.5% to 1.5% C, greater than 10.0% and less than 15.0% Cr, 2.5% to 5.0% Ni, and the remainder is Fe.

[0038] In the manufacturing method of the Fe-Mn alloy of the first and second embodiments, the ingot has a γ-Fe phase and an α phase as a crystal structure. Preferably, the area fraction of the γ-Fe phase is 50% or more, and the area fraction of the α phase is less than 50%. As a result, a phase transformation to the β-Mn phase is easily generated during the solidification heat treatment.

[0039] Next, the ingot is subjected to hot working to obtain a hot-worked product. As hot working, hot hammer forging is performed (step S2), and then hot groove roll rolling (S3) is performed. Thus, a bar material as a hot-worked product is obtained. Hot working is performed at a temperature of 1100°C to 1250°C. The obtained hot-worked product is water-cooled.

[0040] The hot-worked product has the same component composition and area fraction of the crystal structure as the ingot. The size of the metal grains of the hot-worked product is preferably 10 μm or less. As a result, the Fe-Mn alloy as the final product has high hardness. The processing rate of hot working is preferably 45% to 80%. The processing rate is the reduction rate of the cross-sectional area. That is, the processing rate is the value obtained by subtracting the ratio of the cross-sectional area of ​​the bar as the material after processing to the cross-sectional area of ​​the ingot as the material before processing from 1. The processing rate of hot working is 45% to 80%, and the size of the metal grains is 10 μm or less.

[0041] Next, the hot-worked product after water cooling is subjected to cold working to produce a cold-rolled material as a cold-worked product. As cold working, cold rotary forging (step S4), cold wire drawing (step S5), and cold roll rolling (step S6) are performed.

[0042] Cold rotary forging (step S4) is a process of cold forging a hot-worked bar to obtain a thin bar with a narrowed outer diameter. Cold wire drawing (step S5) is a process of drawing a thin bar using a diamond die to obtain a wire drawing material. Cold roll rolling (step S6) is a process of rolling a wire drawing material in such a way that the cross section of the wire drawing material changes from a circle to a rectangle to obtain a cold rolled material. In this way, a strip-shaped strip can be obtained as a cold rolled material.

[0043] Dislocations are introduced into the metal crystals of the thin bars obtained by cold rotary forging (step S4), the wire drawing materials obtained by cold wire drawing (step S5), and the strips obtained by cold rolling (step S6). The processing rate of cold working is preferably 20% or more and 90% or less, and more preferably 40% or more and 80% or less. Thus, an appropriate amount of dislocations are introduced into the metal crystals, and a phase transition from the γ-Fe phase to the β-Mn phase of the crystal structure is easily generated, so that the hairspring 1 as the final product can have a desired hardness. In addition, since the β-Mn phase has a higher hardness than the γ-Fe phase, the area fraction of the β-Mn phase is preferably greater than the area fraction of the γ-Fe phase in the Fe-Mn alloy. Thus, the hairspring 1 as the final product can have a desired hardness.

[0044] The cold-rolled material has the same component composition and area fraction of the crystal structure as the ingot. The size of the metal crystal grains of the cold-rolled material is preferably 10 μm or less. This allows the hairspring 1 as the final product to have a desired hardness.

[0045] Next, in the plastic working step (step S7 ), the strip material as the cold-rolled material is cut into a predetermined length and then held in a spiral shape using a jig or the like, whereby the strip material is formed into the shape of the hairspring 1 .

[0046] Finally, in the solidification heat treatment step (step S8), the formed cold-rolled material is subjected to solidification heat treatment to obtain the hairspring 1. The solidification heat treatment causes a phase transition from the γ-Fe phase to the β-Mn phase.

[0047] The curing heat treatment is performed at a temperature of 550°C to 800°C. Preferably, the curing heat treatment is performed at a temperature of 600°C to 700°C. Thus, the hairspring 1 as the final product can have a desired hardness. If the temperature of the curing heat treatment is too high, the hardness of the hairspring 1 may decrease. In addition, the curing heat treatment is performed for 10 minutes to 12 hours. Thus, the area fraction of the β-Mn phase of the Fe-Mn alloy is 50% or more, and the hairspring 1 can have a low magnetic susceptibility and a desired hardness. If the time of the curing heat treatment is too long, the hardness of the hairspring 1 may decrease. The hairspring 1 obtained by the curing heat treatment is air-cooled.

[0048] The hairspring 1 obtained by the solidification heat treatment has the same component composition and area fraction of the crystal structure as the ingot. In addition, the hairspring 1 has an α phase and a β-Mn phase as a crystal structure, and the area fraction of the β-Mn phase is 50% or more. The hairspring 1 has a β-Mn phase with an area fraction of 50% or more, and therefore has a low magnetic susceptibility.

[0049] In the method for manufacturing the hairspring 1, a homogenization heat treatment step may be performed on the ingot before the hot working step. The homogenization heat treatment is performed at, for example, 1000° C. to 1200° C. for 0.5 to 3 hours. Thus, the metal crystals of the ingot become uniform.

[0050] In the method for manufacturing the hairspring 1, an annealing step may be performed between the hot working step and the cold working step to anneal the hot worked product obtained in the hot working step. The annealing is performed at, for example, 1000° C. to 1200° C. for 0.5 to 3 hours. Thus, the metal crystals of the hot worked product become uniform.

[0051] The method for manufacturing the hairspring 1 is not limited to the above-mentioned example, and the hairspring 1 may be manufactured by a manufacturing method different from the above-mentioned manufacturing method.

[0052] Those skilled in the art will appreciate that various changes, substitutions and modifications can be made to the present invention without departing from the spirit and scope of the present invention. Example 1

[0053] Hereinafter, the above-mentioned embodiment will be described in more detail based on examples, but the present invention is not limited to these examples.

[0054] <Example 1> Materials were weighed to have a composition ratio of 35.0% Mn, 8.0% Al, 1.5% C, 10.0% Cr, 5.0% Ni, and the remainder Fe by mass%. Using these materials, the steps other than the plastic working step (step S7) in the above-mentioned manufacturing method were performed to manufacture a strip of Fe-Mn alloy. In the manufacturing method, the processing rate of hot working was 70%, and the processing rate of cold working was 80%. In addition, the solidification heat treatment was performed at 600°C for 12 hours.

[0055] <Example 2> Materials were weighed to have a composition ratio of 31.0% Mn, 5.0% Al, 0.5% C, 5.0% Cr, 2.5% Ni, and the remainder Fe. Using these materials, a Fe-Mn alloy strip was produced by the same production method as in Example 1.

[0056] <Example 3> Materials were weighed to have a composition ratio of 30.0% Mn, 5.0% Al, 1.0% C, 15.0% Cr, 5.0% Ni, and the remainder Fe. Using these materials, a Fe-Mn alloy strip was produced by the same production method as in Example 1.

[0057] <Example 4> Materials were weighed to have a composition ratio of 31.0% Mn, 3.0% Al, 0.5% C, 5.0% Cr, 2.5% Ni, and the remainder Fe. Using these materials, a Fe-Mn alloy strip was produced by the same production method as in Example 1.

[0058] <Example 5> Materials were weighed to have a composition ratio of 31.0% Mn, 2.0% Al, 0.5% C, 5.0% Cr, 2.5% Ni, and the remainder Fe. Using these materials, a Fe-Mn alloy strip was produced by the same production method as in Example 1.

[0059] <Example 6> Materials were weighed to have a composition ratio of 31.0% Mn, 1.0% Al, 0.5% C, 5.0% Cr, 2.5% Ni, and the remainder Fe. Using these materials, a Fe-Mn alloy strip was produced by the same production method as in Example 1.

[0060] <Comparative Example 1> Materials were weighed to have a composition ratio of 30.0% Mn, 8.0% Al, 1.0% C, 10.0% Cr, 5.0% Ni, and the remainder Fe. Using these materials, a Fe-Mn alloy strip was produced by the same production method as in Example 1.

[0061] <Comparative Example 2> The materials were weighed to have a composition ratio of 31.0% Mn, 5.0% Al, and the remainder Fe by mass %. Using these materials, a Fe-Mn alloy strip was produced by the same production method as in Example 1.

[0062] <Comparative Example 3> Materials were weighed to have a composition ratio of 31.0% Mn, 0.5% C, 5.0% Cr, 2.5% Ni, and the remainder Fe by mass %. Using these materials, a Fe-Mn alloy strip was produced by the same production method as in Example 1.

[0063] <Area Fraction Measurement> The ribbons finally obtained in Examples 1 to 6 and Comparative Examples 1 and 3 were observed using a reflection electron microscope. Specifically, the ribbon was cut in the radial direction, the cut surface was polished using a polishing plate of a rotary polishing device, and the obtained smooth surface was observed.

[0064] Figure 3 (A) is a SEM image of Comparative Example 1 before heat treatment, and the observation magnification is 5000 times. Figure 3(B) is the SEM image of Example 2 before heat treatment, and the observation magnification is 200 times. The gray part 2 of the SEM image is the γ-Fe phase, and the black part 3 is the α phase. The area of ​​the SEM image and the area of ​​the γ-Fe phase are measured. In addition, the area fraction refers to the ratio of the area of ​​a specific phase to the area observed in the SEM image. That is, the area fraction of the γ-Fe phase refers to the ratio of the area of ​​the γ-Fe phase to the area observed in the SEM image.

[0065] Figure 3 (A) and (B) are images before heat treatment, but due to the curing heat treatment, a phase transition to a β-Mn phase occurs in at least a portion of the γ-Fe phase, so that a γ-Fe phase and a β-Mn phase are observed in the SEM image of the cross section of the strip after heat treatment. As described above, in the strip after heat treatment, the sum of the area fraction of the γ-Fe phase and the area fraction of the β-Mn phase is calculated as the area fraction. The area fraction of the γ-Fe phase before heat treatment is approximately equal to the sum of the area fraction of the γ-Fe phase and the area fraction of the β-Mn phase after heat treatment.

[0066] <Magnetic Characteristics Evaluation> The magnetic susceptibility was measured for the strips finally obtained in Examples 1 to 6 and Comparative Examples 1 and 3. The test pieces with a thickness of 3 mm obtained by cutting the strips were measured. Specifically, a magnetic field with a maximum magnetic field of -398 [kA / m] to +398 [kA / m] (-4900 [G] to +4900 [G]) was applied to the test pieces, and the magnetic susceptibility was calculated from the magnetization curve (MH curve) obtained by measuring the magnetization of the test pieces.

[0067] <Processability Evaluation> The materials weighed in the composition ratios shown in Examples 1-6 and Comparative Examples 1-3 were used to perform the steps of the above-mentioned manufacturing method including the plastic working step (step S7). If the strip obtained in the steps before step S6 can be formed into a hairspring shape in step S7, it is evaluated that the workability is sufficient, and if it cannot be formed, it is evaluated that the workability is insufficient. The case where it cannot be formed includes the case where the hardness is too high and it is difficult to form, and the case where it is broken during the forming process due to brittleness.

[0068] Table 1 shows the composition ratios of Examples 1 to 6 and Comparative Examples 1 to 3, the area fraction of the γ-Fe phase of the final strip, the magnetic susceptibility, and the results of the workability evaluation. The results of the workability evaluation are indicated as "Y" when the workability is sufficient, and "N" when the workability is insufficient.

[0069] [Table 1]

[0070] The area fractions of the γ-Fe phase in the strips of Examples 1 and 3 and Comparative Example 1 were 74%, 80%, and 45%, respectively. In addition, the area fractions of the γ-Fe phase in the strips of Examples 2 and 4 to 6 and Comparative Example 3 were all greater than 99%.

[0071] The magnetic susceptibilities of the strips of Examples 1 to 6 are 0.024, 0.003, 0.002, 0.003, 0.002, and 0.005, respectively, which are all small values ​​below 0.03 and suitable for use as a hairspring. Therefore, it is believed that the hairspring formed using these strips also has a suitable magnetic susceptibility. In contrast, the magnetic susceptibility of the strip of Comparative Example 1 is 0.2, which is insufficient for use as a hairspring. This is because in the strip of Comparative Example 1, the M, which is a fine carbide showing magnetism, is formed due to the solidification heat treatment. 23 The precipitation of C6 (M is Fe, Mn or Cr) contributes to the increase of magnetic susceptibility. Therefore, it is considered that the hairspring formed using this strip does not have a suitable magnetic susceptibility.

[0072] The strip of Comparative Example 2 was broken during the cold working process due to its brittleness, and therefore the processing rate was evaluated as insufficient, and the area fraction and magnetic susceptibility were not measured. The strip of Comparative Example 3 was broken during the plastic working process, and therefore the processing rate was evaluated as insufficient, and the area fraction was not measured. Therefore, it is considered that the strips of Comparative Examples 2 and 3 are not suitable for use in hairsprings.

Claims

1. A Fe-Mn alloy, characterized in that: The composition includes the following in mass %: Manganese (Mn) greater than 30.0% and less than 35.0%, 1.0% to 8.0% aluminum (Al), 0.5% to 1.5% carbon (C), 5.0% to 10.0% chromium (Cr), 2.5% to 5.0% nickel (Ni), The rest is iron (Fe), The crystalline structure includes a γ-Fe phase or a β-Mn phase, and the sum of the area fraction of the γ-Fe phase and the area fraction of the β-Mn phase is 50% or more.

2. A Fe-Mn alloy, characterized in that: The composition includes the following in mass %: 25.0% to 30.0% manganese (Mn), 1.0% to 8.0% aluminum (Al), 0.5% to 1.5% carbon (C), More than 10.0% and less than 15.0% of chromium (Cr), 2.5% to 5.0% nickel (Ni), The rest is iron (Fe), The crystalline structure includes a γ-Fe phase or a β-Mn phase, and the sum of the area fraction of the γ-Fe phase and the area fraction of the β-Mn phase is 50% or more.

3. The Fe-Mn alloy according to claim 1 or 2, characterized in that: The magnetic susceptibility is less than 0.

030.

4. The Fe-Mn alloy according to claim 1 or 2, characterized in that: The sum of the area fraction of the γ-Fe phase and the area fraction of the β-Mn phase is 80% or more.

5. The Fe-Mn alloy according to claim 1 or 2, characterized in that: The area fraction of the β-Mn phase is greater than the area fraction of the γ-Fe phase.

6. A hairspring for a watch, characterized in that: Made of the Fe—Mn alloy according to claim 1 or 2.

7. A method for producing a Fe-Mn alloy, characterized in that: Include: A hot working step of hot working the ingot to obtain a hot worked product; A cold working step of cold working the hot worked product to obtain a cold worked product; and a step of subjecting the cold worked product to a hardening heat treatment to obtain a Fe-Mn alloy, The composition of the Fe-Mn alloy includes, by mass %, the following: Manganese (Mn) greater than 30.0% and less than 35.0%, 1.0% to 8.0% aluminum (Al), 0.5% to 1.5% carbon (C), 5.0% to 10.0% chromium (Cr), 2.5% to 5.0% nickel (Ni), The rest is iron (Fe), The crystalline structure includes a γ-Fe phase or a β-Mn phase, and the sum of the area fraction of the γ-Fe phase and the area fraction of the β-Mn phase is 50% or more.

8. A method for producing a Fe-Mn alloy, characterized in that: Include: A hot working step of hot working the ingot to obtain a hot worked product; A cold working step of cold working the hot worked product to obtain a cold worked product; and a step of subjecting the cold worked product to a hardening heat treatment to obtain a Fe-Mn alloy, The composition of the Fe-Mn alloy includes, by mass %, the following: 25.0% to 30.0% manganese (Mn), 1.0% to 8.0% aluminum (Al), 0.5% to 1.5% carbon (C), More than 10.0% and less than 15.0% of chromium (Cr), 2.5% to 5.0% nickel (Ni), The rest is iron (Fe), The crystal structure includes a γ-Fe phase or a β-Mn phase, and the sum of the area fraction of the γ-Fe phase and the area fraction of the β-Mn phase is 50% or more.

Citation Information

Patent Citations

  • Clock resonator

    JP2020501006A